Holding the Lid: Suspension Techniques to Prevent Lower Eyelid Ectropion—A Systematic Review - Yalcin, Can Ege (Facial Plastic Surgery, 2025)
Lower eyelid ectropion is a challenging postoperative complication that can affect both function and aesthetics. Preventative strategies are critical, particularly in high-risk periocular and midface surgeries.This review aims to evaluate the efficacy and variety of prophylactic suspension techniques used to prevent lower eyelid ectropion. Primary outcome: Incidence of ectropion; secondary outcomes: Technique tolerability and reported complications.Systematic review conducted in accordance with PRISMA guidelines.A systematic search was performed through June 2025 using keywords: “Frost suture,” “suspension,” “ectropion,” “tape,” and “prevention.” Sixteen studies were included (9 clinical, 8 technical). Data on patient indications, techniques, outcomes, and follow-up were extracted.Techniques included Frost sutures, periosteal anchoring, barbed sutures, external splinting, and forehead hitch. Ectropion prevention was generally successful, though one clinical study reported no significant benefit with Frost suture use.Multiple prophylactic strategies appear effective, but evidence quality is low. Higher-level comparative studies are needed.
Keywords: lower eyelid ectropion; prophylactic suspension techniques; frost suture; barbed suture; periosteal anchoring